2008
DOI: 10.1074/jbc.m706760200
|View full text |Cite
|
Sign up to set email alerts
|

The Rac1 Polybasic Region Is Required for Interaction with Its Effector PRK1

Abstract: Protein kinase C-related kinase 1 (PRK1 or PKN) is involved in regulation of the intermediate filaments of the actin cytoskeleton, as well as having effects on processes as diverse as mitotic timing and apoptosis. It is activated by interacting with the Rho family small G proteins and arachidonic acid or by caspase cleavage. We have previously shown that the HR1b of PRK1 binds exclusively to Rac1, whereas the HR1a domain binds to both Rac1 and RhoA. Here, we have determined the solution structure of the HR1b-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
80
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(85 citation statements)
references
References 49 publications
5
80
0
Order By: Relevance
“…In addition, we have demonstrated that MCP1-induced VSMC migration and proliferation require PKN1 (22), a Rho GTPase effector (30). However, many studies have reported that Pak1, a Cdc42/Rac1 effector, plays an essential role in the regulation of cell migration and proliferation (31,32).…”
Section: Pak1 Mediates Mcp1-induced Hasmc F-actin Stress Fibermentioning
confidence: 99%
“…In addition, we have demonstrated that MCP1-induced VSMC migration and proliferation require PKN1 (22), a Rho GTPase effector (30). However, many studies have reported that Pak1, a Cdc42/Rac1 effector, plays an essential role in the regulation of cell migration and proliferation (31,32).…”
Section: Pak1 Mediates Mcp1-induced Hasmc F-actin Stress Fibermentioning
confidence: 99%
“…This small region shows striking sequence diversity among related GTPases, which has been linked to their differential localization to intracellular membranes, nuclear translocation as well as binding to regulatory-and effector-proteins. [12][13][14][15] In the early '90s, a series of studies established the functional importance of the HVR of Rac GTPases by focusing on its role in the activation of the NADPH oxidase complex. This complex was, at the time, already identified as an established Rac effector, responsible for production of reactive oxygen species in granulocytes.…”
Section: The Rac1 Hypervariable Region In Targeting and Signalingmentioning
confidence: 99%
“…Intriguingly, the analysis by Modha et al suggested that the Rac1 C-terminus has a rather fixed structure comprising a proline-based α-helix, followed by an extended stretch of large basic residues. 15 Importantly, the C-terminal portion of this region (Lys 183-Arg185) was proposed to loop back to interact with the core G-domain, in particular with portions of the switch II region and the region C-terminal to helix 3. In addition, several of the basic residues in the PBR contact the cognate binding region in PRK1.…”
mentioning
confidence: 99%
See 2 more Smart Citations